Analysis of the Impact of Fiscal Decentralization Policies on Indonesia's Economic Growth During the Covid-19 Pandemic - Purnomo, Muhammad Eko; Suman, Agus; Susilo, Susilo (Journal of International Conference Proceedings, 2023)
The Covid-19 pandemic has put pressure on the global economy and Indonesia. The impact of Covid-19 is the largest since the 2008 Global Financial Crisis. This study aims to describe the fiscal policies pursued by the Indonesian government in response to the crisis during the pandemic, as well as to examine the influence of balancing funds and capital expenditures on local own-source revenues and their impact on the economic growth rate in 34 provinces in Indonesia. The results of this study showed Indonesian government's success in implementing a flexible fiscal policy with various fiscal stimulus has had a positive impact on the handling of the Covid-19 pandemic in Indonesia both from a health and economic perspective. Based on the results of the path analysis, the balancing funds and local own-source revenue variables have a significant influence on the economic growth rate, while the capital expenditure variable does not have a significant influence on the economic growth rate.